Photosynthesizing on metal excess: Copper differently induced changes in various photosynthetic parameters in copper tolerant and sensitive Silene paradoxa L. populations. (March 2015) - Bazihizina, Nadia; Colzi, Ilaria; Giorni, Elisabetta; Mancuso, Stefano; Gonnelli, Cristina
Highlights: Cu effects on photosynthesis were studied in Cu-tolerant Silene paradoxa . The most limiting factor to photosynthesis seemed Cu-imposed stomatal closure. The photosynthetic machinery showed enhanced Cu tolerance. Cu tolerance evolution resulted also in adaptation at the photosynthetic level. Abstract: This work investigated Cu-induced changes in photosynthetic activity in contrasting populations of Silene paradoxa L. A metallicolous Cu-tolerant population and a non-metallicolous sensitive population were grown in hydroponics and exposed to different CuSO4 treatments for different times. Copper accumulation, MDA concentrations, and several photosynthetic parameters were measured to assess different effects of Cu exposure on plants from the two populations. A more efficient ability to photosynthesize in the presence of Cu excess was showed by the Cu-tolerant population with respect to the sensitive one. Interestingly, Cu-imposed limitations were present not only at a different degree, but also of different nature in the two populations. In the tolerant population, the most limiting factor to photosynthesis seemed to be Cu-imposed stomatal closure, whereas Cu-mediated biochemical limitation was scarce and Cu-mediated reduction in mesophyll conductance almost non-existent. In the sensitive population, Cu largely affected all the measured parameters, so that its photosynthetic activity experienced any kind of limitation, diffusional and especially biochemical. The lower Cu concentrations accumulated in the tolerant plant could be one of the factors concurring to the reported differences in photosynthetic activity, but also a higher capacity of internal detoxification and compartmentalization of the metal could not be excluded.